Accounting and Digital Marketing Assistance for MSMEs In the Covid 19 Pandemic Period - Erna Retno Rahadjeng; Endang Dwi Wahyuni; Driana Leniwwati (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
This service aims to assist partners in making simple financial reports and assist in developing digital marketing in the form of web creation to introduce their business to the community. The problem faced by partners, especially in the field of fast food, is the lack of information about managing finances and developing marketing, so as a servant trying to provide solutions for partners to be able to enlarge their business by identifying business costs and adding a wider marketing system, namely by creating a web to market products. Therefore, the community service wants to try to solve the problems faced by partners, among others, by helping to identify the operational costs incurred to compile correct financial reports, besides that the service team also helps in developing digital marketing in the form of web creation to introduce their business to the public. The method implemented in community service is a model of mentoring and training in making financial reports and making digital marketing. Assistance is carried out step by step and continuously until partners can make financial reports independently. In addition, assistance in creating a web for their business through WA, Facebook, Instagram, and Twitter in the hope of increasing sales of the products. With the assistance provided by the service team, it is hoped that partners will be able to develop and survive during this COVID-19 pandemic. As a result of this assistance, partners are able to make financial reports independently and already have a business website that is spread through WhatsApp, Instagram, and Twitter. The service team will also always carry out monitoring and evaluation on a regular basis so that partners are able to prepare independent financial reports correctly and are also able to operate digital marketing that has been created. Keywords: MSMEs, Fintech Lending, accounting and digital marketing